The Middle East in the Politics of the Great Mongol Ulus in the Years 1248–1258 – An Outline of the Issues - Szewczyk, Rafał (Vade Nobiscum, tom XXIV/2024: Studia nad Bliskim Wschodem, 2024)
The Mongol presence in the Middle East had a major impact on shaping the destiny of this region in the 13th century. The conquest of these territories was a complex process that continued until the following century. The aim of this article is to discuss a segment of this process: the years 1248–1258. The text illuminates the problems associated with the Mongol Empireʼs internal politics, as well as tracing the Hülegü campaign and the leaderʼs diplomatic efforts leading to the defeat of the Assassins and the conquest of the Baghdad Caliphate in 1258.